Selective laser melting of ceramic particles strengthened stainless steel - Zhai, Wengang (Nanyang Technological University, 2023)
316L austenitic stainless steel is widely used because of its excellent corrosion resistance, but its low strength limits its engineering applications. Yield strength of wrought 316L can be as low as 170 MPa according to ASTM A240. Efforts have been made to fabricate ceramic particles strengthened stainless steel composites. The usual way to make stainless steel composites is through powder metallurgy route, but the method usually requires complex and expensive post processing such as hot rolling and hot isostatic pressing. Moreover, undesirable coarse grains and heterogeneous distribution of reinforcements are often observed. In contrast, selective laser melting (SLM), or it can be called laser powder bed fusion (LPBF), is potentially a simple method to fabricate dispersed particles strengthened composites, because its small melting zone (~100 μm in width and depth) and fast cooling rate (106 - 108 K/s) help to prevent the particles from segregation. In this work, the microstructure and mechanical properties of 316L and ceramic particles (Y2O3, TiC and TiB2) strengthened 316L prepared using SLM were investigated. The powder feedstock was mixed using low energy ball milling process. This method is efficient and has a negligible effect on the shape and flowability of 316L powder. The ceramic particles are uniformly distributed on the 316L powder surface. After SLM, Y2O3 particles tend to agglomerate while TiC particles are uniformly distributed in 316L matrix. Y2O3 particles have a slight effect on the strength of 316L but decrease the elongation due to the formation of agglomeration. Grain size is 25.9 μm, 18.8 μm and 3.2 μm for selective laser melted 316L, 316L-1TiC and 316L-3TiC respectively, showing that the addition of TiC particles can refine the grain size remarkably. Interestingly, the addition of TiB2 particles not only significantly refined the grains but also produced a unique core-shell melt pool structure. High fraction of twin boundaries was observed with the addition of TiC and TiB2 particles. Y2O3 has neglectable effect on the strengthening for 316L. The yield strength, ultimate tensile strength and elongation of SLM 316L (609 MPa, 722 MPa, and 62%), 316L-1TiC (660 MPa, 856 MPa, and 55%), 316L-3TiC (832 MPa, 1032 MPa, and 29%) and 316L-1TiB2 (858 MPa, 1095 MPa, and 27%) show that the addition of TiC and TiB2 particles can significantly strengthen 316L while maintaining good ductility. TiB2 is more effective than TiC on strengthening for 316L. The strength enhancement is mainly achieved through grain refinement and Orowan strengthening. The melting of TiC and TiB2 particles during SLM process is demonstrated by adding pure Ti powder and annealing of 316L-3TiC and 316L-1TiB2 samples. Adding pure Ti to 316L promotes the grain refinement of 316L to 0.8 μm for 316L-3Ti. High fraction of twin boundaries was observed with the addition of pure Ti. In-situ formed TiC nanoparticles were observed in as-built 316L-TiC. After annealing, high number density TiC nanoprecipitations are generated in the matrix. For the as-built 316L-1TiB2, no TiB2 particles were observed. After annealing, Laves phase and Cr boride particles were observed. The observations of the above-mentioned features demonstrated the TiC and TiB2 particles are melted and decomposed during SLM process.